Green synthetic routes to alginate-graphene oxide composite hydrogels with enhanced physical properties for bioengineering applications. (June 2018) - Serrano-Aroca, Ángel; Iskandar, Lilis; Deb, Sanjukta
Graphical abstract: Highlights: New composites with enhanced mechanical, thermal, wettability and water diffusion. Green and sustainable synthesis without consuming thermal or sonic energy. Clean and facile technology that exhibits affordable large-scale production. Crosslinking of graphene oxide nanosheets by coordination chemistry. Improvement of several alginate's physical properties at the same time. Abstract: Hydrogels are being increasingly utilized in bioengineering applications such as tissue engineering because they are able to mimic the specific environments of extracellular matrices and in bioprocess engineering to immobilise cells or enzymes as catalysts. Alginate hydrogels holds great promise in these industrial fields, however, they are mechanically weak, which necessitates composites or hybrid materials to modulate their properties without compromising other important physical properties such as water diffusion, which plays a very important role in the nutrient exchange with the surrounding environment. Efforts to fabricate alginate-based composites reinforced with graphene oxide (GO) have been reported, however there are challenges in enhancing mechanical and other physical properties at the same time, and facile large-scale production. In this study, we report two novel green engineering routes of fabricating calcium alginate-GO hydrogels and compare with the conventional procedure to synthesise alginates via bulk chelation with calcium chloride. The two new methods yielded nanocomposites with significant increases in tensile modulus (up to 2.5 times) and markedly faster water diffusion (>4 times) in comparison to the conventional method. In addition, wettability and thermal properties were also enhanced, which was attributed to the novel structure organisation.